ANALISIS FAKTOR KINERJA ORGANISASI BUMDES-LKM DI KABUPATEN SUMBAWA (Suatu Pendekatan Perspektif Balanced Scorecard) - , Muhammad Sofyan Yahya Putra, Drs. Ahmad Jamli, M.A. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
This research aimed to: (1) conduct an analysis of organizational performance drivers of Microfinance Institutions in Sumbawa regency as a Village-owned Enterprises (BUMDES-LKM), with balanced scorecard perspective approach, (2) to assess the balance of its performance from all four perspectives in explaining organizational performance, (3) to assess the most dominant perspective explaining organizational performance BUMDES-LKM in Sumbawa regency. This study also conducted an analysis of organizational needs of customer satisfaction aspects in an effort to maintain customer retention and acquisition. Second-order confirmatory factor analysis is used as an analytical tool, using "SPSS Amos' version 18th as software as well as maximum likelihood estimation method. There are 27 items of questions in the questionnaire, and 50 number of respondents. Due to the large number of items in the question, while relatively small sample size, so as to avoid the occurrence of heywood-case and non-convergent solutions, the data were analyzed using a composite indicator to obtain a reliable estimate. The results showed that the performance of financial perspective, customer perspective, internal business process perspective, and learning and growth perspective is the factor organizational performance drivers BUMDES-LKM in Sumbawa regency. When compared with other perspectives, learning and growth perspective is not yet balanced like the balance performance concept in balanced scorecard perspective, of which characterized by the low ability variable of learning and growth perspective in explaining organizational performance. Financial perspective is the most dominant factor explaining organizational performance BUMDES-LKM in Sumbawa regency. Viewed from customer satisfaction aspect, at this moment the priority of organizational needs to BUMDES-LKM in Sumbawa regency as an effort to maintain customer retention and acquisition is improving organizational performance against responsiveness of service, professionalism, and speed of transactions.